Discovery of a Novel General Anesthetic Chemotype Using High-throughput Screening - McKinstry-Wu, Andrew R. (Anesthesiology, 2015)
BACKGROUND: The development of novel anesthetics has historically been a process of combined serendipity and empiricism, with most recent new anesthetics developed via modification of existing anesthetic structures. METHODS: Using a novel high-throughput screen employing the fluorescent anesthetic 1-aminoanthracene (1-AMA) and apoferritin as a surrogate for on-pathway anesthetic protein target(s), we screened a 350,000 compound library for competition with 1-AMA-apoferritin binding. Hit compounds meeting structural criteria had their binding affinities for apoferritin quantified with isothermal titration calorimetry and were tested for γ-aminobutyric acid type A-receptor binding using a flunitrazepam binding assay. Chemotypes with a strong presence in the top 700 and exhibiting activity via isothermal titration calorimetry were selected for medicinal chemistry optimization including testing for anesthetic potency and toxicity in an in vivo Xenopus laevis tadpole assay. Compounds with low toxicity and high potency were tested for anesthetic potency in mice. RESULTS: From an initial chemical library of over 350,000 compounds, we identified 2,600 compounds that potently inhibited 1-AMA binding to apoferritin. A subset of compounds chosen by structural criteria (700) was successfully reconfirmed using the initial assay. Based upon a strong presence in both the initial and secondary screens the 6-phenylpyridazin-3(2H)-one chemotype was assessed for anesthetic activity in tadpoles. Medicinal chemistry efforts identified four compounds with high potency and low toxicity in tadpoles, two were found to be effective novel anesthetics in mice. CONCLUSIONS: We demonstrate the first use of a high-throughput screen to successfully identify a novel anesthetic chemotype and show mammalian anesthetic activity for members of that chemotype.